2008
DOI: 10.1007/s10072-008-0896-3
|View full text |Cite
|
Sign up to set email alerts
|

Human psyche and headache: tension-type headache

Abstract: The role of psychological factors related to headache, particularly tension-type headache (TTH), has long been a focus of investigation. The subject at issue is a complex one, with some aspects that are still being debated by experts. In episodic TTH, it is possible to hypothesise that headache is not only a "primary" headache that causes gratuitous pain to sufferers. In fact, it might represent an improper mode of communicating the sufferers' intimate discomfort, caused by an inadequate relationship between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 16 publications
1
22
1
1
Order By: Relevance
“…Although the lines of study may differ, there seems to be agreement that these conditions overlap with anxiety, depression, maladaptive coping, inability to communicate with others and deal with life events, and common pathophysiological origins 7,[19][20][21][22][23][24][25] . The results from the present study further add to the discussion on the very high prevalence of signs and symptoms of TMD among primary headache patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although the lines of study may differ, there seems to be agreement that these conditions overlap with anxiety, depression, maladaptive coping, inability to communicate with others and deal with life events, and common pathophysiological origins 7,[19][20][21][22][23][24][25] . The results from the present study further add to the discussion on the very high prevalence of signs and symptoms of TMD among primary headache patients.…”
Section: Discussionmentioning
confidence: 99%
“…The role of psychological factors and psychiatric diseases in headache, particularly TTH, long has been a focus of investigation [24]. The point is complex, with some aspects that still are being debated.…”
Section: Comorbidities Of Tension-type Headachementioning
confidence: 99%
“…Similarly to MS, also headache appears to be closely correlated with depressive symptoms, particularly when disease becomes chronic causing feelings of inadequacy, negative thinking, diminished interest for environment and relationships, affecting patients’ quality of life – QoL (Blomkvist et al, 2002; Manack et al, 2011). In the last decade, however, it has been suggested that depressive and anxious features, as well as other psychological aspects, may be a distinctive characteristic of this population of patients, instead of a consequence of experimenting chronic pain (Mongini et al, 2000; Torelli et al, 2008; Berry and Drummond, 2014; Bottiroli et al, 2016; Muñoz et al, 2016). In ALS population, by contrast, Major Depressive Disorder (MDD) seems to be an uncommon result, with a prevalence similar to that of the adult general population (Norris et al, 2010).…”
Section: Introductionmentioning
confidence: 99%